Ethiopathogenesis of caseous lymphadenitis in goats - Mahmood, Zaid Khudhur (2015)
Caseous lymphadenitis (CLA) is an economically important disease of sheep and goats worldwide. However, paucity of literature on CLA research in goats in Malaysia led to this study to investigate the mechanism by which Corynebacterium pseudotuberculosis and its exotoxin, phospholipase D (PLD) adversely affects reproduction in mice and goats. This study was also designed to test the hypothesis that acute phase proteins, specifically, haptoglobin and serum amyloid A can be used as diagnostic biomarkers for CLA. One hundred and five clinically healthy mice of both sexes aged between 10 to 12 weeks, weighing 25-35 g and twenty six clinically healthy crossbred Boer goats (13 bucks and 13 does) aged between 12 to 14 months, weighing 30-35 kg were used in this study. The does were non-pregnant, non-lactating and have been housed separately from the bucks. At the beginning of the experiments, two types of inoculum were used that involved live C. pseudotuberculosis and its exotoxin, PLD. The mice were divided into three equal groups of 35 mice each. The crossbred Boer goats were also divided into three groups, the first group consisted of 6 goats, the second group consisted of 10 goats and the third group consisted of 10 goats. The control groups 1 (mice and goats) were inoculated with sterile phosphate buffered saline (PBS 1 ml/mouse intra-peritoneal and 1 ml/goat subcutaneous) whereas group 2 were inoculated with live C. pseudotuberculosis (1x109 cfu intra-peritoneal in mice and subcutaneous in goats) and group 3 were inoculated with PLD (1 mllmouse intra-peritoneal and 1 ml/20 kg B.W. in goats). Mice were observed during the entire experiment, blood was collected into heparinized tubes for sex hormones analyses. Post mortem examination of gross lesions was conducted on ovaries, uterus, testes and epididymis and tissue samples were fixed for histopathological examination. Goats were also observed during the entire experiment for clinical signs and serial blood collections were conducted. Blood was placed into heparinized, plain, EDTA and sodium citrate tubes for acute phase proteins (APPs), haematology and sex hormones analyses. Post mortem examination of gross lesions was conducted on lungs, heart, liver, spleen, kidneys and lymph nodes and tissue samples were fixed for histopathology and cellular changes were scored. Mice inoculated with C. pseudotuberculosis showed significant decrease (p<O.05) in testosterone concentration. Both inoculated groups showed no gross changes in the reproductive organs. However, microscopic examination revealed that C. pseudotuberculosis inoculation caused congestion, oedema, infiltration of inflammatory cells, degeneration and necrosis in the ovaries, uterus, testes and epididymis. In addition, mice in PLD inoculated group showed congestion, degeneration and necrosis in the ovaries, uterus, testes and epididymis as well as thrombosis in the ovaries and uterus only. Goats inoculated with both C. pseudotuberculosis and PLD showed significant increase (p<O.05) in haptoglobin concentration with significant decrease (p<O.05) in albumin concentration. Goats also showed significant increase (p<O.05) in body temperature, heart rate, respiratory rate during different times of the experiment post inoculation with both C. pseudotuberculosis and PLD. Moreover, body score showed significant decrease (p<O.05) in both treated groups toward the end of the experiment. Additionally, the site of inoculation and the superficial lymph nodes showed abscess formation in C. pseudotuberculosis inoculated group only. Corynebacterium pseudotuberculosis inoculated goats showed significant decrease (p<O.05) in red blood cell count, haemoglobin, creatine phosphokinase concentrations and significant increase (p<O.05) in neutrophils count. Both C. pseudotuberculosis and PLD inoculated goats showed significant increase (p<O.05) in packed cell volume, mean corpuscular volume, white blood cells, lymphocytes, monocytes, eosinophils and basophils counts and aspartate transaminase, total bilirubin, calcium, creatinine, gamma glutamyltransferase, urea, total protein, globulin, lactate dehydrogenase concentrations, prothrombin time and activated partial thromboplastin time whilst both inoculated groups showed significant decrease (p<O.05) in mean corpuscular haemoglobin concentration, neutrophils count, alanine transaminase and alkaline phosphatase concentrations. Inoculation with PLD showed significant decrease (p<O.05) in creatine phosphokinase concentration. Testosterone, progesterone, estrogen hormones, scrotal circumference and semen volume, pH, wave pattern, motility and concentration showed significant decrease (p<O.05) post inoculation with C. pseudotuberculosis and PLD. In addition, dead sperm and abnormal sperm percentage showed significant increased (p<O.O~) in both treated groups. Microscopic examination of the ovaries showed fibrous tissue formation post inoculation with C. pseudotuberculosis, whilst in PLD inoculated group the ovaries showed severe congestion, degeneration and necrosis of the stromal cells. In addition, the uterine tissues showed congestion, degeneration and necrosis post inoculation with both C. pseudotuberculosis and PLD. The testes showed irregular and shrinkage of seminiferous tubules with oedema, degeneration and necrosis of spermatogonia cells and Leydig cells post inoculation with both C. pseudotuberculosis and PLD. Similarly, the epididymis showed oedema, degeneration and necrosis of the lining epithelium of the epididymal tubules post inoculation with both C. pseudotuberculosis and PLD. Corynebacterium pseudotuberculosis inoculated group showed gross changes in lungs represented by grey and red hepatization, deeper inside, spots of congestion and abscess formation. The heart appeared oedematous and the pericardium showed some degree of opacity. The liver showed multiple abscess formation on its surface. The kidneys appeared friable with opaque capsule whilst the spleen showed mosaic appearance. The Iym.ph nodes appeared enlarged, fluctuating and filled with purulent pus. The PLD Inoculated group also showed gross changes in the lung represented by some spots of grey hepatization with no abscess formation in its parenchyma. T~e he~rt showed no obvious gross changes. The liver appeared congested With white line along the edges of almost all the liver lobes. The kidneys ~ppear~d congested with opaque spots on its capsule. The spleen appeared friable With mosaic appearance. The lymph nodes showed no abscess formation; however, when cut, it revealed a rusty yellow discoloration. Microscopic examination of C. pseudotuberculosis inoculated group showed significant congestion, oedema, and infiltration of inflammatory cells, degeneration and necrosis in the lungs, heart, liver, kidneys and spleen. The lymph nodes also showed significant granuloma formation with micro-foci of abscess formation. The PLD inoculated group showed significant congestion, oedema, degeneration and necrosis. In addition, hepatic tissue showed significant increase (p<O.05) in Kupffer cells number. The lymph nodes showed no abscess formation with some haemosiderin deposits. Therefore, from this study, it can be concluded that C. pseudotuberculosis had detrimental effects on testosterone concentration and reproductive organs in mice. However, in goats, C. pseudotuberculosis and PLD had negative effects on testosterone, estrogen and progesterone hormone concentrations as well as semen quality and reproductive organs in both genders. Acute phase reactant. mainly, haptoglobin, showed Significant sensitivity in both treated groups; this sensitivity may have potential as diagnostic biomarker for CLA in goats. Similarly, C. pseudotuberculosis resulted in classical clinical manifestation of CLA specifically abscess formation in superficial lymph nodes, yet, PLD, showed different clinical manifestation with no abscessation. In addition, C. pseudotuberculosis and PLD showed significant changes in all haematological parameters, yet, PLD showed different response pattern which may indicate a different mechanism of action. The gross and cellular changes were of typical CLA lesions in C. pseudotuberculosis inoculated group whilst PLD inoculated group showed less gross changes; however, the cellular changes were severe, this may indicate or reflect the toxic effects of PLD on tissues.